Main histological parameters to be evaluated in an experimental model of myocardial infarct treated by stem cells on pigs - García Gómez-Heras,Soledad; Largo,Carlota; Larrea,Jose Luis; Vega-Clemente,Luz; Calderón Flores,Miguel; Ruiz-Pérez,Daniel; García-Olmo,Damián; García-Arranz,Mariano (PeerJ, 2019)
Myocardial infarction has been carefully studied in numerous experimental models. Most of these models are based on electrophysiological and functional data, and pay less attention to histological discoveries. During the last decade, treatment using advanced therapies, mainly cell therapy, has prevailed from among all the options to be studied for treating myocardial infarction. In our study we wanted to show the fundamental histological parameters to be evaluated during the development of an infarction on an experimental model as well as treatment with mesenchymal stem cells derived from adipose tissue applied intra-lesionally. The fundamental parameters to study in infarcted tissue at the histological level are the cells involved in the inflammatory process (lymphocytes, macrophages and M2, neutrophils, mast cells and plasma cells), neovascularization processes (capillaries and arterioles) and cardiac cells (cardiomyocytes and Purkinje fibers). In our study, we used intramyocardial injection of mesenchymal stem cells into the myocardial infarction area 1 hour after arterial occlusion and allowed 1 month of evolution before analyzing the modifications on the normal tissue inflammatory infiltrate. Acute inflammation was shortened, leading to chronic inflammation with abundant plasma cells and mast cells and complete disappearance of neutrophils. Another benefit was an increase in the number of vessels formed. Cardiomyocytes and Purkinje fibers were better conserved, both from a structural and metabolic point of view, possibly leading to reduced morbidity in the long term. With this study we present the main histological aspects to be evaluated in future assays, complementing or explaining the electrophysiological and functional findings.
Keywords: Pig; Myocardical infarction; Histological parameters; ASC